Involvement of 5-HT1A/1B receptors in the antinociceptive effect of paracetamol in the rat formalin test - A. Roca-Vinardell; E. Berrocoso; M. Llorca-Torralba; J.A. García-Partida; J. Gibert-Rahola; J.A. Mico (Neurobiology of Pain, 2018)
The mechanism of analgesic action of paracetamol (acetominophen) remains still unknown. However, a relationship between serotonergic system and the effect of paracetamol has been previously demonstrated. The serotonin activity in the brainstem is primarily under the control of 5-HT1A somatodendritic receptors, although some data also suggest the involvement of 5-HT1B receptors. To determine whether the 5-HT1A and 5-HT1B receptors are involved in the antinociceptive effect of paracetamol, we evaluated the effect of paracetamol (0.125–1 g/kg i.p.) followed by different antagonists [WAY 100,635 (0.8 mg/kg s.c.) and SB 216,641 (0.8 mg/kg s.c.)] or agonists [8-OH-DPAT (0.125 mg/kg s.c.) and CP 93,129 (0.125 mg/kg s.c.)] of 5-HT1A and 5-HT1B receptors, respectively, in the rat model of formalin-induced pain. We demonstrated that paracetamol administration showed a dose-dependent antinociceptive effect in the formalin test. WAY 100,635 (5-HT1A antagonist) induced an increase in the antinociceptive effect of paracetamol at 250 mg/kg doses. Conversely, 8-OH-DPAT (5-HT1A agonist) decreased the antinociceptive effect of paracetamol at 500–1000 mg/kg doses. However, SB216641 (5-HT1B antagonist) modified weakly the antinociceptive effect of paracetamol at 250 mg/kg doses and CP 93,129 (5-HT1B agonist) not produce a clear effect in the antinociceptive effect of paracetamol. These results suggest that the antinociceptive effect of paracetamol can be enhanced mainly by compounds having 5-HT1A antagonist properties in the formalin test and maybe by 5-HT1B receptors antagonists. Keywords: Paracetamol, Formalin test, 5-HT1A receptors, 5-HT1B receptors, Antinociceptive effect